Islamic Education Curriculum and Learning Activities in Islamic Education - Mudzakkir, Ahmad; Mustami, Khalifah; Ondeng, Syarifuddin (Educational Journal of Learning Technology, 2025)
The Islamic education curriculum plays an important role in shaping students' personalities, morals, and spirituality by integrating religious and scientific values. This article uses the literature review method to examine the application of the Islamic education curriculum and its learning activities in various Islamic educational institutions. This curriculum integrates Islamic values in cognitive, affective, and psychomotor aspects. In addition to emphasizing academic achievement, the curriculum also focuses on forming an Islamic character. The learning activities implemented are contextual, experience-based, and supported by technology tailored to Islamic values. The findings show that the Islamic education curriculum is holistic, balancing spiritual and academic aspects. Regular evaluation of the curriculum is needed so that Islamic education remains relevant and can produce a knowledgeable generation with Islamic character and ready to contribute to society.